CARACTERISTICS AND PROSPECTS FOR DEVELOPEMNT OF LEGAL AND REGULATORY SUPPORT OF EXPERNAL INDEPENDENT ASSESSMENT IN UKRAINE - Головко, Світлана Григорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: to analyze the main stages of the formation of a system of legislative external independent assessment in Ukraine and to highlight the perspective directions of its improvement. Methods: the norms of educational law are analysed concerning the realisation of the regulatory function, which determines, in particular, legal norms of interaction of subjects in the process of preparation and implementation of external independent assessment. The emphasis is placed on the importance of basic laws (Laws of Ukraine «On Education», «On Higher Education») in the development of the external independent assessment system, its methodology and technologies. Using the method of synthesis, the system of legal and regulatory support to implement external independent assessment is considered as a functional subsystem of educational law, which is a complex institution regulating relations between subjects of educational activity. Results: the article describes the potential of the legislation on education of Ukraine in providing external independent assessment, defining its methodology based on the principles of validity (substantiation and feasibility of assessment methods and technologies to assess the concrete aims), openness and transparency, objectivity, reliability, accessibility, correspondence; the position on formation in the whole system of legal and regulatory support of external independent assessment as an important component of educational law and its main components (basic legal act of educational law, legislative acts regulating relations in the area of education, regulations, and local legal norms) are substantiated. The conclusion is made on the availability of legal and organisational conditions for the effective functioning of external independent assessment and its development. The perspective directions of development of legal and regulatory support of external independent assessment in the context of educational reforms are determined. Discussion: the issue of the regulation of external independent assessment procedures at different levels of education is updated. The prospects of expanding its functions as an instrument for monitoring the state of the educational system prior to the establishment of effective tools for quality education management are considered.